Implications of money-back guarantees for individual retirement accounts: Protection then and now - Vanya Horneff; Daniel Liebler; Raimond Maurer; Olivia S. Mitchell (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
In the wake of the financial crisis and continued volatility in international capital markets, there is growing interest in mechanisms that can protect people against retirement account volatility. This paper explores the consequences for savers' wellbeing of implementing market-based retirement account guarantees, using a life cycle consumption and portfolio choice model where investors have access to stocks, bonds, and tax-qualified retirement accounts. We evaluate the case of German Riester plans adopted in 2002, an individual retirement account produce that includes embedded mandatory money-back guarantees. These guarantees influenced participant consumption, saving, and investment behavior in the higher interest rate environment of that era, and they have even larger impacts in a low-return world such as the present. Importantly, we conclude that abandoning these guarantees could enhance old-age consumption for over 80% of retirees, particularly lower earners, without harming consumption during the accumulation phase. Our results are of general interest for other countries implementing default investment options in individual retirement accounts, such as the U.S. 401(k) defined contribution plans and the Pan European Pension Product (PEPP) recently launched by the European Parliament.
urn:nbn:de:hebis:30:3-514913
Keywords: D14; D91; G11; 330; individual retirement account; investment guarantee; longevity risk; retirement income; lifecycle model